Stay healthy your choice - Tan, Hui Meng; Ng, Chirk Jenn (Utusan Publications & Distributors : in collaboration with The Faculty of Medicine, University of Malaya, the Ministry of Women, Family and Community Development, 2010)
This book is a guide for men and those who want to know more about men's health. This health guide is not meant to provide detailed and comprehensive medical information; intead, we include only men's health problems which commonly affect men in Malaysia.